Social work values and ethics - Reamer, Frederic G., 1953- (Foundations of social work knowledge., 2018)
"For decades, teachers and practitioners have turned to Frederic G. Reamer's Social Work Values and Ethics as the leading introduction to ethical decision making, dilemmas, and professional conduct in practice. A case-driven, concise, and comprehensive textbook for undergraduate and graduate social work programs, this book surveys the most critical issues for social work practitioners.The fifth edition incorporates significant updates to the National Association of Social Workers Code of Ethics and new practice and model regulatory standards used by social service and licensing agencies around the world. Reamer also focuses on how social workers should navigate the digital world through discussion of the ethical issues that arise from practitioner use of online services and social networking sites to deliver services, communicate with clients, and provide information to the public, and what standards will protect confidential information transmitted electronically. He highlights potential conflicts between professional ethics and legal guidelines and expands discussions of informed consent, confidentiality and privileged communication, boundaries and dual relationships, documentation, conflicts of interest, and risk management. Conceptually rich and attuned to the complexities of ethical decision making, Social Work Values and Ethics is unique in striking the right balance among history, theory, and practical application." --